Country breakout session highlights. (December 2016) - Ghezzi, Angelo; Filli, Linard; Solaro, Claudio; Mekies, Claude; Landete, Lamberto; Lycke, Jan
At the 2016 MS Experts Summit, country-relevant aspects pertaining to the management of symptoms and disability in multiple sclerosis (MS), with emphasis on those associated with spasticity, were explored in interactive country breakout sessions chaired by selected MS experts. Attendees had the opportunity to review and discuss topics in their own native language. After feedback from each session leader, key messages were collated and presented in a Plenary Session by Summit chair, Professor Angelo Ghezzi. Topics at this year's Summit included: gait tracking (Germany/Switzerland); the Care Alliance against MS spasticity (Italy); MS spasticity and associated symptoms (France); improvement in MS symptoms and functionality and patients' independence (Spain); Swedish MS guidelines (Sweden/Rest of World).